What's Behind the Billboard: Dead Men and Private Parts. Object? Sign? Thing? - Peter Schofer (Studies in 20th & 21st Century Literature, 1996)
It is a truism that objects and visual sign systems convey meaning. But the meanings shift radically according to the viewer and how the signs are read. Several years ago I asked an American student to photograph scenes which either shocked her or perplexed her upon her arrival in France. One photo is of a publicity panel at the entry to Le Père Lachaise cemetery. The panel consisted of nine magazine covers, including covers for magazines on children, cooking, hunting, and computers, as well as two pornographic magazines. The young student focused on just the last two covers, thus masking out the others to create her shocked meaning. Other viewers, such as a housewife, would have been expected to mask out the pornographic magazines and be enticed by the magazines centered on the home. A more global reading of the billboard reveals rhetorical links, narratives, and ironical juxtapositions between the magazines, thus creating dispersed and contradictory meanings drawn from this miniature map of contemporary France.
Keywords: truism; objects; visual sign system; sign; convey; viewer; read; reader; American student; shocked; photograph; perplexed; France; Le Père Lachaise cemetery; magazine covers; pornographic; meaning; create; rhetorical links; narratives; ironical juxtapositions; contradictory meaning; contemporary France